Method for producing polysuccinimide, polysuccinimide composition and polyaspartic acid composition
By performing chain extension reaction on the preliminary polyylbutyl ester of medium molecular weight, the problem of difficulty in producing high molecular weight polyylbutyl ester in the prior art is solved, efficient and simple industrial production is achieved, and the application basis for high molecular weight polyylbutyl ester and its derivatives is provided.
Patent Information
- Application Number
- JP2023172282
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-10-03
- Publication Date
- 2025-04-15
AI Technical Summary
It is difficult to effectively produce high molecular weight polysuccinimide in the prior art, and the traditional methods are complex and it is difficult to achieve industrial production.
By performing a chain extension reaction of a preliminary polyylbutyl ester with a medium molecular weight, a multi-step reaction is carried out using different equipment, and the reaction conditions are controlled to obtain a high molecular weight polyylbutyl ester.
It realizes efficient and simple production of high molecular weight polyylbutyl ester, meets industrial production needs, and provides a foundation for its derived multifunctional materials.
Smart Images

Figure 2025062917000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing polysuccinimide, a polysuccinimide composition, and a polyaspartic acid composition. [Background technology]
[0002] Polyaspartic acid, obtained by hydrolysis of polysuccinimide (also called polysuccinimide), is a biodegradable polycarboxylic acid, and is expected to be an alternative material because its chemical structure is similar to that of polyacrylic acid. A known method for producing polyaspartic acid from aspartic acid is to produce polysuccinimide, and then hydrolyze it with an alkali to produce polyaspartic acid. An example of a method for producing polysuccinimide is a method in which a dehydration condensation reaction is carried out with aspartic acid in the presence of an acidic catalyst to produce polysuccinimide (for example, Patent Document 1). However, the molecular weight of the polysuccinimide generally obtained is low, and the applications in which it can be used are limited, and even if it can be used, it does not have a very high performance. Therefore, as a method for obtaining a high molecular weight polysuccinimide, a method has been disclosed in which a catalyst and a polymerization promoter are added to a polymerization system and polymerized to obtain a high molecular weight polysuccinimide-based (co)polymer (e.g., Patent Document 2). In addition, a method has been disclosed in which a mixture containing aspartic acid and an acid catalyst is polycondensed to produce a solid low molecular weight polymer mixture containing a low molecular weight polysuccinimide, and then an acid catalyst is added and polycondensed to produce a high molecular weight polysuccinimide (e.g., Patent Document 3). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Japanese Patent Application Publication No. 8-231710 [Patent Document 2] Japanese Patent Application Publication No. 9-302088 [Patent Document 3] JP 2001-335635 A Summary of the Invention [Problem to be solved by the invention]
[0004] However, the weight average molecular weight of the polysuccinimide obtained in Patent Document 2 is about 30000 to 43000. Therefore, polysuccinimide having a higher molecular weight is required. In addition, the production method in Patent Document 3 is complicated and not necessarily satisfactory as an industrial production method. An object of the present invention is to provide a method for producing polysuccinimide, which can easily produce polysuccinimide having a high molecular weight (for example, weight average molecular weight: 100,000 to 500,000). [Means for solving the problem]
[0005] The subject matter of the present invention includes the following embodiments. [1] A method for producing a polysuccinimide, comprising the steps of: producing a second polysuccinimide from a polysuccinimide composition containing a first polysuccinimide, carrying out a chain extension reaction of the first polysuccinimide to obtain a second polysuccinimide; A method for producing a polysuccinimide, wherein the weight average molecular weight (Mw) of the first polysuccinimide is in the range of 25,000 to 50,000, and the proportion of dicarboxylic acid in the polysuccinimide composition is 1.5 to 4 mol %. [2] The chain extension step is a second step, and before the chain extension step, as a first step, The method further includes a polycondensation step of performing a polycondensation reaction of aspartic acid to obtain a polysuccinimide composition containing a first polysuccinimide, The method for producing polysuccinimide according to [1], wherein the first step and the second step are carried out in different apparatuses. [3] The method for producing a polysuccinimide according to [2], wherein the first step is terminated and transition is made to the second step when the weight average molecular weight (Mw) of the first polysuccinimide in the first step is in the range of 25,000 to 50,000 and the ratio of dicarboxylic acid in the first polysuccinimide is in the range of 1.5 to 4 mol %. [4] The method for producing polysuccinimide according to [2] or [3], wherein the first step is carried out using a continuous kneader. [5] The method for producing polysuccinimide according to any one of [1] to [4], wherein the second step is carried out using at least one device selected from the group consisting of a hot air conveying type dryer, a material stirring type dryer, a fluidized bed dryer, a material conveying and stationary type dryer, a cylindrical dryer, an infrared dryer, a microwave dryer, and a superheated steam dryer. [6] A polysuccinimide obtained by the method for producing a polysuccinimide according to any one of [1] to [5], A polysuccinimide composition containing a second polysuccinimide having a weight average molecular weight in the range of 100,000 to 500,000. [7] A polyaspartic acid composition which is a hydrolysate of the polysuccinimide composition according to [6]. [8] A crosslinked polyaspartic acid composition which is a crosslinking reaction product of the polyaspartic acid composition described in [7]. [9] A thickener for cosmetics containing the crosslinked polyaspartic acid composition according to [8].
[10] A water-absorbing composition comprising the crosslinked polyaspartic acid composition according to [8]. Effect of the Invention
[0006] According to the present invention, there can be provided a method for producing polysuccinimide, which can easily produce high molecular weight polysuccinimide. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0007] (Production method of polysuccinimide) A method for producing a polysuccinimide according to one embodiment of the present invention (a method for producing a polysuccinimide according to the present embodiment, or simply a method for producing a polysuccinimide according to the present embodiment) is a method for producing a second polysuccinimide by using a polysuccinimide composition containing a first polysuccinimide. The method includes a chain extension step of carrying out a chain extension reaction of the first polysuccinimide to obtain a second polysuccinimide. The weight average molecular weight (Mw) of the first polysuccinimide is in the range of 25,000 to 50,000, and the proportion of dicarboxylic acid in the polysuccinimide composition is 1.5 to 4 mol%. It is preferable that the chain extension step is the second step, and that the method further includes a first step prior to the chain extension step, in which a polycondensation reaction of aspartic acid is carried out to obtain a polysuccinimide composition containing a first polysuccinimide. It is preferable that the first step and the second step are carried out in different reaction apparatuses.
[0008] [Aspartic acid] The aspartic acid according to this embodiment may be an L-form, a D-form, or a mixture thereof that is abundant in nature. It may be any of the L-form, D-form, and DL-form. Furthermore, if aspartic acid can be used in the reaction system of the first step, it may include a salt of aspartic acid, or an anhydrous or hydrated form (eg, monohydrate, dihydrate) of aspartic acid or a salt thereof.
[0009] [Polysuccinimide and polysuccinimide composition] The structure of the polysuccinimide according to this embodiment may be a linear structure or a branched structure.
[0010] The polysuccinimide composition containing the first polysuccinimide according to this embodiment (sometimes referred to as the first polysuccinimide composition) is a mixture of reaction products obtained in the first step in the method for producing polysuccinimide according to this embodiment. The first polysuccinimide composition contains the first polysuccinimide which is the reaction product of the first step, and may contain a catalyst and a solvent blended as necessary, and may contain unreacted aspartic acid depending on the reaction conditions. In the first step, the content of the first polysuccinimide in the first polysuccinimide composition depends on the reaction conditions and is not particularly limited. For example, it may be 45 mass% or more, 50 mass% or more, or 55 mass% or more. It may be 80 mass% or less, 70 mass% or less, or 65 mass% or less. The first polysuccinimide is a term used to distinguish it from the final polysuccinimide (second polysuccinimide) obtained in the second step of the production method of this embodiment, and means a crude polysuccinimide or a precursor of the second polysuccinimide. In the production method of this embodiment, the second polysuccinimide has a higher average weight molecular weight than the first polysuccinimide. The ratio (Mw1 / Mw2) of the average weight molecular weight (Mw2) of the second polysuccinimide to the average weight molecular weight (Mw1) of the first polysuccinimide may be 1.2 or more, 1.5 or more, or 2.0. It is preferably 2.5 or more, and more preferably 3.0 or more. It may be 10.0 or less, or 7.0 or less.
[0011] The weight average molecular weight (Mw) of the first polysuccinimide is preferably in the range of 25,000 to 50,000, more preferably in the range of 25,000 to 45,000, and further preferably in the range of 25,000 to 40,000. The method for measuring the weight average molecular weight of polysuccinimide will be described in detail in the Examples.
[0012] The ratio of dicarboxylic acid in the first polysuccinimide composition is preferably 1.5 to 4 mol %, more preferably 2 to 4 mol %, and further preferably 2.5 to 4 mol %. The method for measuring the proportion of dicarboxylic acid in the first polysuccinimide composition will be described in detail in the Examples. The first polysuccinimide preferably has a weight average molecular weight (Mw) in the range of 25,000 to 50,000, and the proportion of dicarboxylic acid in the polysuccinimide composition is 1.5 to 4 mol%. The first polysuccinimide more preferably has a weight average molecular weight (Mw) in the range of 25,000 to 45,000, and the proportion of dicarboxylic acid in the polysuccinimide composition is 2 to 4 mol%. The first polysuccinimide further preferably has a weight average molecular weight (Mw) in the range of 25,000 to 40,000, and the proportion of dicarboxylic acid in the polysuccinimide composition is 2.5 to 4 mol%.
[0013] The polysuccinimide (second polysuccinimide) obtained by the method for producing polysuccinimide of the present embodiment may have a weight average molecular weight in the range of 100,000 to 50,0000, 110,000 to 300,000, or 120,000 to 200,000.
[0014] [Polycondensation step (1st step)] The method for producing polysuccinimide of this embodiment may directly use the above-mentioned first polysuccinimide to carry out a chain elongation step (second step) described in detail below, but preferably includes a polycondensation step as the first step prior to the chain elongation step. In the first step, the polycondensation reaction of aspartic acid may be obtained by solid-state polymerization, solubilizing solvent polymerization, insolubilizing solvent polymerization, or a method of thermally polymerizing an ammonium salt and / or amide of at least one acid selected from the group consisting of maleic acid, fumaric acid, and malic acid, and among these, the polysuccinimide obtained by solid-state polymerization is preferred. As the solid-phase polymerization, there is mentioned a method in which aspartic acid is directly subjected to a thermal polycondensation reaction in a solid phase. In the first step of the production method of the present embodiment, preparing a polysuccinimide composition containing a first polysuccinimide obtained by solid-state polymerization of aspartic acid is advantageous for the chain extension reaction in the second step of the production method of the present embodiment.
[0015] In the first step of the method for producing polysuccinimide of this embodiment, the polycondensation reaction of aspartic acid is preferably carried out by polycondensing a mixture of aspartic acid and an acid catalyst.
[0016] In this embodiment, "polycondensation" means polycondensation in which two water molecules are dehydrated from aspartic acid to produce polysuccinimide. However, other side reactions and intermediate production reactions may be included. For example, an amidation reaction in which one water molecule is dehydrated from aspartic acid before the ring is closed to form an imide ring, and a deammonia reaction from aspartic acid are included. That is, in the first step of this embodiment, a polymer (first polysuccinimide) having a succinimide structure as a repeating unit is synthesized. However, the final product of the first step of this embodiment is a polysuccinimide composition containing the polymer (first polysuccinimide). The polysuccinimide composition may contain monomer units contained due to side reactions, etc. In addition, the polysuccinimide composition may contain unreacted aspartic acid.
[0017] <Acidic catalyst> The acid catalyst according to the present embodiment is not particularly limited, but examples thereof include phosphorus oxyacids, sulfuric acid, sulfurous acid, alkylsulfonic acids, arylsulfonic acids, chloric acid, chlorous acid, hypochlorous acid, bromic acid, bromous acid, hypobromous acid, iodic acid, iodous acid, hypoiodous acid, molybdic acid, tungstic acid, hydrochloric acid, hydrogen sulfide, hydrogen bromide, sodium bisulfate, potassium bisulfate, ammonium bisulfate, and fluorosulfuric acid.
[0018] The acid catalyst according to the present embodiment is particularly preferably a phosphorus oxygen acid. Specific examples of phosphorus oxygen acids include orthophosphoric acid, metaphosphoric acid, pyrophosphoric acid, polyphosphoric acid, phosphorus pentoxide, hypophosphorous acid, orthophosphorous acid, heterophosphorous acid, pyrophosphoric acid, hypophosphoric acid, heterophosphoric acid, pyrophosphoric acid, alkylphosphonic acid, arylphosphonic acid, phosphoric acid ester containing at least one acidic hydrogen, and phosphoric acid ester containing at least one acidic hydrogen. These may be used alone or in combination of two or more. Among these, those that can be in a solution state or a slurry state under reaction conditions and can uniformly disperse aspartic acid or its condensate are preferred, and orthophosphoric acid and polyphosphoric acid are particularly preferred.
[0019] The acid catalyst may be in a state of being diluted with a solvent (e.g., a polar solvent such as water, alcohol, or ketone). The acid catalyst may be used at a concentration of preferably 50% by mass or more, more preferably 60% by mass, particularly preferably 70% by mass or more, most preferably 80% by mass or more, and preferably 90% by mass or less. For example, when phosphoric acid is used, the concentration of the phosphoric acid solution is preferably 60% by mass or more, more preferably 80% by mass, and particularly preferably 85% by mass or more. If the acid catalyst concentration is moderately high, the amount of solvent to be removed during the polymerization operation is generally reduced, which is advantageous in terms of energy saving.
[0020] <Reaction Apparatus> In the first step according to the present embodiment, for example, when an acid catalyst is used, the method of mixing the mixture containing aspartic acid and the acid catalyst is not particularly limited. Any method capable of uniformly mixing the two may be used. The amount of the acid catalyst in the first step is not sufficient to completely dissolve aspartic acid at room temperature or reaction temperature, so mixing with stirring is preferred. From an industrial point of view, mechanical mixing is preferred, which is suitable for mixing a large amount of solid and liquid.
[0021] The mixing device used for mechanical mixing is not particularly limited, and various batch mixers and continuous mixers known in the art can be used. Specific examples of batch mixers include double planetary mixers, double arm kneaders, and stationary tank mixers such as gate mixers, share bar mixers, and helical blade mixers. In addition, bulk mixers such as ribbon mixers, cone and screw mixers, pan-muller mixers, and plow mixers can also be mentioned. Specific examples of continuous mixers include single-shaft and twin-shaft screw mixers, pug mills, and the like.
[0022] In the first step according to this embodiment, when an acidic catalyst is used, a mixture containing aspartic acid and the acidic catalyst may be mixed, and then the polycondensation reaction of aspartic acid may be carried out, or the polycondensation reaction of aspartic acid may be carried out while the mixture containing aspartic acid and the acidic catalyst is being mixed.
[0023] The polycondensation reaction of aspartic acid is preferably solid-phase polymerization. The apparatus for performing solid-phase polymerization is not particularly limited, and includes batch-type or continuous-type apparatus. The batch-type apparatus and the continuous-type apparatus may be vertical or horizontal, respectively. The apparatus for performing solid-phase polymerization includes, for example, an apparatus for performing continuous or batch-type operation. The solid-phase polymerization may be performed using at least one apparatus selected from the group consisting of, for example, a hot air transfer type dryer, a material agitation type dryer (such as a fluidized bed dryer), a material conveying and stationary type dryer, a cylindrical dryer, an infrared dryer, a microwave dryer, and a superheated steam dryer. The solid-phase polymerization may also be performed using at least one apparatus selected from the group consisting of, for example, a fluidized bed reactor, a moving bed reactor, a fixed bed reactor, and an agitation dryer type reactor.
[0024] "Feeding speed (discharge amount)" The first step according to the present embodiment is preferably carried out using a continuous kneader, and is preferably a continuous kneader equipped with a heating mechanism using a jacket or electric heater capable of heating the inside. The stirring blade for mixing may be a single shaft or a multi-shaft of two or more shafts. As a continuous kneader having such a form, a twin-screw extruder (extruder), which is generally called an extruder, or a twin-screw continuous kneader, etc., can be mentioned as a preferred device form. The feed rate of the continuous kneader (discharge rate) varies depending on the size of the continuous kneader, so it cannot be generally stated. It is necessary to select a feed rate that will give the first polysuccinimide a weight average molecular weight (Mw) in the range of 25,000 to 50,000. In general, if the feed rate is slow, the weight average molecular weight of the polysuccinimide obtained will be large, and as the feed rate increases, the weight average molecular weight will decrease. Although there are restrictions depending on the device, the longer the residence time in the device, the higher the molecular weight. Furthermore, the screw rotation speed also affects the molecular weight, and the faster the rotation speed, the more shear energy is applied, so the molecular weight increases. By controlling the feed rate, rotation speed, and reaction temperature described later, it is possible to control the weight average molecular weight of the polysuccinimide and the amount of dicarboxylic acid.
[0025] <Solvent> In the first step according to this embodiment, the mixing operation of the raw materials (aspartic acid, and the acid catalyst when an acid catalyst is used) is usually carried out by direct mixing, but in some cases, the aspartic acid and / or the acid catalyst may be dissolved or dispersed in a solvent (polar solvent such as water, alcohol, ketone, etc.). However, it is preferable to thoroughly remove solvents other than water from the system before the start of the reaction in order to prevent side reactions. In addition, the operation of mixing the acid catalyst and aspartic acid can be carried out more efficiently by utilizing water generated by the condensation reaction of aspartic acid.
[0026] <Reaction temperature> In the first step according to the present embodiment, when an acid catalyst is used, the temperature at which the mixture containing aspartic acid and the acid catalyst is mixed is not particularly limited, but when polycondensation is carried out after aspartic acid and the acid catalyst are sufficiently mixed, a method of mixing at a low temperature such as room temperature may be used. However, it is an effective mixing method to mix at a temperature at which polycondensation does not proceed rapidly. The reason is that the solubility of aspartic acid increases by increasing the temperature, and also because a part of it becomes polysuccinimide, which increases the solubility in the acid catalyst and may allow uniform mixing.
[0027] In the first step according to the present embodiment, when an acid catalyst is used, a mixture containing aspartic acid and an acid catalyst prepared in advance is polycondensed at 150 to 230°C. The temperature at this time is preferably 170 to 225°C, more preferably 190 to 220°C. By appropriately increasing this temperature, the degree of polymerization can be increased and the process time can be shortened. Conversely, by appropriately decreasing this temperature, thermal decomposition and side reactions can be prevented. In the first step according to this embodiment, when an acidic catalyst is used, the mixture containing aspartic acid and the acidic catalyst may be mixed while the temperature is raised to the polycondensation temperature to carry out polycondensation.
[0028] <Reaction pressure> In the first step according to this embodiment, the pressure in the system during the polycondensation reaction may be normal pressure, slightly pressurized, or negative pressure. The former is, for example, a method of distilling off the water generated while flowing an inert gas, and the latter is, for example, a method of distilling off the water generated by lowering the vapor pressure. In these methods, the state of the polymer mixture may be such that a degree of polymerization is obtained that allows it to be handled as a solid, and that it can be further advanced to a desired degree of polymerization in a subsequent step.
[0029] When the solid-state polymerization is carried out using an inert gas, it is preferable to continuously feed the inert gas to the reaction system. In this case, the inert gas is contacted with the mixture in a countercurrent or parallel current manner. Alternatively, the inert gas can be used as a heat transfer medium to heat the mixture by direct contact.
[0030] When an inert gas is used, the pressure of the reaction system may be any of a negative pressure system, a normal pressure system, and a pressurized system. The pressure is preferably 1 to 5×10 7 [Pa], more preferably 1×10 to 1×10 7 [Pa], particularly preferably 1×10 2 ~5×10 6 [Pa]. Even in the case of a pressurized system, if the pressure is appropriately low, a high-pressure reactor is not required. On the other hand, even in the case of a negative pressure system, if the pressure is appropriately high, there is no need to design a device that can withstand a high vacuum.
[0031] In the first step according to the present embodiment, the normal pressure solid-phase polymerization operation is preferably carried out by passing an inert gas through the system. The amount of the inert gas used is in the range of 0.0001 to 100 L / min, preferably 0.001 to 60 L / min, more preferably 0.01 to 40 L / min, particularly preferably 0.05 to 30 L / min, and most preferably 0.5 to 20 L / min. Here, the inert gas may be, for example, nitrogen. Furthermore, the amount of inert gas used per 1 kg of the mass of aspartic acid, which is the starting material in the first step, is 4.5 to 90 L / min, preferably 10 to 50 L / min, and more preferably 20 to 30 L / min.
[0032] <Response time> The time required for the first step according to this embodiment varies depending on the L / D, supply rate, rotation speed, etc. of the reaction section of the continuous kneader, but is generally 0.017 to 1 hour, preferably 0.033 to 0.5 hours, more preferably 0.05 to 0.33 hours, and particularly preferably 0.083 to 0.25 hours.
[0033] In the first step according to this embodiment, the reaction conditions (acid catalyst, reaction apparatus, reaction temperature, reaction pressure, reaction time, etc.) are appropriately selected to carry out the reaction, and the first step is preferably terminated at a stage where the weight average molecular weight (Mw) of the first polysuccinimide contained in the product of the first step is in the range of 25,000 to 50,000 and the ratio of dicarboxylic acid in the polysuccinimide composition is in the range of 1.5 to 4 mol%. The polysuccinimide composition, which is the product, is preferably transferred directly to the second step described below. The preferred ranges of the weight average molecular weight (Mw) of the first polysuccinimide and the ratio of dicarboxylic acid in the polysuccinimide composition are the same as those described for the product of the first step.
[0034] [Chain extension step (2nd step)] In the chain extension step (second step) according to this embodiment, the chain extension reaction of polysuccinimide means increasing the weight average molecular weight of the first polysuccinimide (molecular weight extension). The method for increasing the weight average molecular weight is not particularly limited, and the main chain or side chain of the polysuccinimide may be extended. The chain extension reaction may also be performed by bonding (for example, crosslinking) the first polysuccinimide molecules together. The chain extension reaction of the polysuccinimide according to this embodiment may be performed by crosslinking with a crosslinking agent, but it is preferable that the chain extension reaction does not include a crosslinking reaction with a crosslinking agent. Here, the meaning of "not including a crosslinking reaction" means that the content of the polysuccinimide generated by the crosslinking reaction in the product produced by the production method according to this embodiment is 0 to 10 mass%, 0 to 5 mass%, or 0 to 1 mass%. In the chain extension step (second step) according to the present embodiment, the chain extension reaction of the polysuccinimide can be, for example, a dehydration condensation reaction, etc. For example, the first polysuccinimide obtained in the first step can be subjected to a dehydration condensation reaction to increase the average weight molecular weight of the polysuccinimide (molecular weight extension), thereby obtaining a second polysuccinimide.
[0035] <Reaction Apparatus> The second step according to this embodiment is carried out in an apparatus different from that used in the first step. In the second step according to the present embodiment, the reaction apparatus used for the chain extension reaction is not particularly limited, and examples thereof include a hot air transfer type dryer, a material agitation type dryer (such as a fluidized bed dryer), a material conveying and stationary type dryer, a cylindrical dryer, an infrared dryer, a microwave dryer, or a superheated steam dryer. The above reaction apparatus is suitable for the dehydration condensation reaction of polysuccinimide. In the second step according to this embodiment, the reaction apparatus used in the chain extension reaction is preferably one selected from the group consisting of a vacuum dryer, a cone dryer, a vibration dryer, and a fluidized bed dryer, and more preferably a vacuum dryer.
[0036] <Solvent> In the second step according to the present embodiment, a solvent other than water may be added as necessary. However, when the first polysuccinimide obtained in the first step is subjected to dehydration condensation to extend the molecular weight, it is preferable not to add a solvent to the polysuccinimide composition obtained in the first step.
[0037] <Reaction temperature> In the second step according to this embodiment, the reaction temperature is preferably 150° C. or higher, more preferably 170° C. or higher, and even more preferably 190° C. or higher. The reaction temperature is preferably 230° C. or lower, more preferably 225° C. or lower, and even more preferably 220° C. or lower.
[0038] <Reaction pressure> In the second step according to this embodiment, the pressure in the system during the chain extension reaction of polysuccinimide may be normal pressure, a slight pressure, or a negative pressure.
[0039] When the solid-state polymerization is carried out using an inert gas, it is preferable to continuously feed the inert gas to the reaction system. In this case, the inert gas is contacted with the mixture in a countercurrent or parallel current manner. Alternatively, the inert gas can be used as a heat transfer medium to heat the mixture by direct contact.
[0040] When an inert gas is used, the pressure of the reaction system may be any of a negative pressure system, a normal pressure system, and a pressurized system. The pressure is preferably 1 to 5×10 7 [Pa], more preferably 1×10 to 1×10 7 [Pa], particularly preferably 1×10 2 ~5×10 6 [Pa]. Even in the case of a pressurized system, if the pressure is appropriately low, a high-pressure reactor is not required. On the other hand, even in the case of a negative pressure system, if the pressure is appropriately high, there is no need to design a device that can withstand a high vacuum.
[0041] In the second step according to this embodiment, the normal pressure solid-phase reaction is preferably carried out by passing an inert gas through the reaction system. The amount of the inert gas used is in the range of 0.0001 to 100 L / min, preferably 0.001 to 60 L / min, more preferably 0.01 to 40 L / min, particularly preferably 0.05 to 30 L / min, and most preferably 0.5 to 20 L / min. Here, the inert gas may be, for example, nitrogen. Furthermore, the amount of inert gas used per 1 kg of the mass of the polysuccinimide composition, which is the starting material in the second step, is 4.5 to 90 L / min, preferably 10 to 50 L / min, and more preferably 20 to 30 L / min.
[0042] <Response time> The time required for the second step according to this embodiment is not particularly limited, but is generally 0.5 to 10 hours, preferably 1 to 8 hours, and more preferably 2 to 7 hours.
[0043] [Post-processing process] The method for producing polysuccinimide of the present embodiment may further include a post-treatment step in addition to the first and second steps. For example, when an acid catalyst is used in the first step, the post-treatment step may include removing the acid catalyst. For example, a polysuccinimide composition (second polysuccinimide composition) containing a second polysuccinimide and an acid catalyst may be washed at 10 to 300° C. with a poor solvent for polysuccinimide (methanol, isopropanol, acetone, water, etc.) to remove the acid catalyst. The washing liquid containing the acid catalyst may be reused in the above washing step after or without a purification step as necessary.
[0044] Furthermore, in the case where an acid catalyst is used in the first step, the acid catalyst contained in the reaction product mixture after the second step according to this embodiment may be dissolved once in a good solvent for polysuccinimide [dimethylformamide (DMF), dimethyl sulfoxide, etc.], and then reprecipitated in a poor solvent for polysuccinimide [methanol, isopropanol, acetone, water, etc.], filtered, and further washed and removed by rinsing with the poor solvent, if necessary.
[0045] (Polysuccinimide composition) The polysuccinimide composition according to one embodiment of the present invention is a polysuccinimide composition (second polysuccinimide composition) containing a second polysuccinimide obtained by the above-mentioned method for producing polysuccinimide according to this embodiment. The weight-average molecular weight of the second polysuccinimide is in the range of 100,000 to 500,000. The weight-average molecular weight of the second polysuccinimide is preferably in the range of 110,000 to 300,000, and more preferably in the range of 120,000 to 200,000. The polysuccinimide composition containing the second polysuccinimide may further contain the acid catalyst mixed in the first step, in addition to the second polysuccinimide.
[0046] (Polyaspartic acid composition) A polyaspartic acid composition according to one embodiment of the present invention (the polyaspartic acid composition according to the present embodiment) is a hydrolysate of a polysuccinimide composition containing the second polysuccinimide obtained by the above-mentioned method for producing polysuccinimide according to the present embodiment. The polyaspartic acid composition of this embodiment can be produced by hydrolyzing the second polysuccinimide using a known hydrolysis reaction method (for example, Non-Patent Document A below). In a more preferred embodiment, the second polysuccinimide is hydrolyzed in the coexistence of an amine compound or the like to obtain a polyaspartic acid composition to which an amine compound is added. Preferred examples of the amine compound include alkylamines having any number of carbon atoms, hydroxyamines having any number of carbon atoms, and diamine compounds. Among these, dodecylamine, 3-amino-1-propanol, 1,2-bis(2-aminoethoxy)ethane, lysine, ornithine, arginine, and the like, or hydrochlorides such as lysine hydrochloride, ornithine hydrochloride, and arginine hydrochloride, and similar sulfates are more preferred.
[0047] [Non-Patent Document A] Journal of Polymer Science: Part A: Polymer Chemistry, Vol. 38, 117-122 (2000)
[0048] The method for producing the polyaspartic acid composition of the present embodiment includes, for example, a step of adding an alkaline aqueous solution to a polysuccinimide composition containing a second polysuccinimide obtained by the method for producing a polysuccinimide of the present embodiment in the coexistence of an amine compound having one or more amino groups in the molecule, its hydrochloride, and its sulfate, thereby hydrolyzing the polysuccinimide to obtain a polyaspartic acid composition to which the amine compound, etc. are added.
[0049] The alkaline aqueous solution preferably has a pH of 10 to 14 at 25°C, and more preferably has a pH of 12 to 14. Specific examples of the alkaline aqueous solution include an aqueous solution of hydroxide or carbonate of an alkaline metal or an alkaline earth metal, and aqueous ammonia. In particular, an aqueous solution of NaOH, KOH, or LiOH is preferred, and an aqueous solution of NaOH is more preferred. There is no particular restriction on the concentration of the base in the alkaline aqueous solution, but a solution of 0.5 to 50 mass % is usually preferred.
[0050] The amount of the alkaline aqueous solution used may be sufficient to convert the polysuccinimide obtained by the method for producing polysuccinimide according to the present embodiment into a polyaspartic acid salt. Usually, there is no problem if the number of moles of the base used is within the range of 90 to 120% of the total number of moles of the carboxyl group and the imide group in the polysuccinimide. The temperature during the treatment with the alkaline aqueous solution may be any temperature that does not cause hydrolysis of the polymer main chain, and is usually preferably 10° C. to 70° C., more preferably 40° C. to 60° C. The time during the treatment with the alkaline aqueous solution is preferably 1 hour to 6 hours.
[0051] The polyaspartate aqueous solution thus obtained can be used as it is, or can be extracted as a powder (i.e., polyaspartate powder) by means of freeze-drying or the like. Also, it can be neutralized with an appropriate acid to be extracted as polyaspartic acid.
[0052] (Crosslinked polyaspartic acid composition) The crosslinked polyaspartic acid composition of one embodiment of the present invention (the crosslinked polyaspartic acid composition of the present embodiment) is a crosslinked reaction product of a polyaspartic acid composition. The polyaspartic acid composition is obtained from the polysuccinimide composition of the present embodiment by a method similar to the method described in the above (Polyaspartic acid composition) section. The polyaspartic acid composition can be crosslinked by a known crosslinking reaction to produce the first crosslinked polyaspartic acid composition of the present embodiment. Alternatively, the crosslinked polyaspartic acid composition may be produced by the method for producing a crosslinked polyaspartic acid composition described below. The method for producing the crosslinked polyaspartic acid composition may be, for example, to a polysuccinimide composition containing the second polysuccinimide obtained by the method for producing polysuccinimide of this embodiment, an alkaline aqueous solution is added in the presence of an amine compound, or its hydrochloride or a similar sulfate, to hydrolyze the polysuccinimide, thereby obtaining a polyaspartic acid composition to which an amine compound or the like is added. Next, a crosslinking agent such as a multifunctional epoxy or diamine compound is added to the obtained polyaspartic acid composition, and the crosslinked polyaspartic acid composition can be produced by reacting the amino group contained in the residue of the amine compound added to the polyaspartic acid skeleton (if it is a multifunctional epoxy) with the carboxy group of the main chain of the polyaspartic acid (if it is a diamine compound). The above-mentioned hydrolysis reaction and crosslinking reaction may be carried out continuously in the same reaction vessel, and the order of adding the raw materials is not particularly limited.
[0053] The polysuccinimide composition (composition containing the second polysuccinimide) obtained by the method for producing polysuccinimide of this embodiment may be used as polysuccinimide as it is. The polysuccinimide according to this embodiment may also be hydrolyzed and crosslinked by the above-mentioned method to be used as polyaspartic acid, crosslinked polyaspartic acid, salts or derivatives of these acids. Among these, polyaspartic acid salts can be used as raw materials for cosmetics (e.g., thickeners, etc.). Examples of cosmetics include skin care cosmetics, makeup cosmetics, hair care cosmetics, and body care cosmetics, such as lotions, beauty serums, milky lotions, creams, packs, eyeliner, eye shadow, mascara, eyebrow products, foundations, face powders, makeup bases, blushers, facial cleansers, hair styling products, hair dyes, hair dyes, bleaches, hair restorers, shampoos, treatments, conditioners, cleansers, lipsticks, glosses, toothpastes, teeth whitening products, sunscreens, body powders, body soaps, hand soaps, deodorants, and bath additives.
[0054] (Uses of the polysuccinimide composition (composition containing the second polysuccinimide) and the crosslinked polyaspartic acid composition) The polysuccinimide composition of this embodiment (a composition containing a second polysuccinimide) and the crosslinked polyaspartic acid composition can be used in a wide variety of applications, including, for example, sanitary products such as sanitary napkins, paper diapers, breast pads, and disposable wipes; medical products such as wound protection dressings, medical underpads, and poultices; pet sheets, portable toilets, gel air fresheners, gel deodorants, sweat-absorbent fibers, and disposable hand warmers; toiletry products such as shampoos, setting gels, and moisturizers; water-retaining materials for agriculture and horticulture, plant growth aids, agents for extending the life of cut flowers, floral foams (materials for fixing cut flowers), seedbeds for raising seedlings, vegetation sheets for hydroponic cultivation, seed tapes, fluid seeding media, and anti-condensation materials. It can be used as agricultural and horticultural supplies such as agricultural sheets for agricultural use, freshness-preserving materials for food trays, food packaging materials such as drip-absorbing sheets, cold storage materials, transport materials such as water-absorbent sheets for transporting fresh vegetables, construction materials for preventing condensation, sealing materials for civil engineering and construction, lost-mud prevention agents for shield construction, concrete admixtures, civil engineering and construction materials such as gaskets and packings, sealing materials for electronic devices and optical fibers, water-stopping materials for communication cables, electrical equipment-related materials such as inkjet recording paper, sludge coagulants, water treatment agents such as dehydration agents for gasoline and oils, water removers, printing glue, water-swelling toys, artificial snow, slow-release fertilizers, slow-release pesticides, slow-release drugs, humidity adjusters, antistatic agents, etc. Among these, when the polysuccinimide composition of the present embodiment (composition containing a second polysuccinimide) and the crosslinked polyaspartic acid composition are used as a water-absorbing composition constituting an absorbent body of an absorbent article such as a diaper or sanitary product, the size (average particle size) is preferably 1 to 5000 μm, more preferably 10 to 1000 μm, and even more preferably 100 to 800 μm.
[0055] Furthermore, the polysuccinimide composition (composition containing the second polysuccinimide) and the crosslinked polyaspartic acid composition of this embodiment can be used as a thickening composition such as a thickener for cosmetics. When used as the above-mentioned thickening composition, the crosslinked polyaspartic acid composition of this embodiment has a size (average particle size) of preferably 150 μm or less, more preferably 100 μm or less, and even more preferably 80 μm or less. (Water absorbent resin)
[0056] The water-absorbing resin according to one embodiment of the present invention (present embodiment) contains the crosslinked polyaspartic acid composition according to the present embodiment. The water-absorbing resin according to the present embodiment may contain other resins other than the crosslinked polyaspartic acid composition according to the present embodiment, or other known additives, if necessary. When the crosslinked polyaspartic acid composition of the present embodiment is a hydrogel-like crosslinked body, the crosslinked body is dried as necessary, and is usually pulverized before or after drying to become a water-absorbent resin. The drying method is not particularly limited, and can be any known method such as heat drying, freeze drying, reduced pressure (vacuum) drying, and reduced pressure heat drying. Since the particle shape may change depending on the drying method, it is selected according to the purpose. In addition, in the case of heat drying, the drying temperature is usually 60°C to 250°C, preferably 80°C to 220°C, and more preferably 100°C to 200°C. In the case of reduced pressure heat drying, the drying temperature is usually 50°C to 200°C, preferably 60°C to 150°C, and more preferably 70°C to 120°C. The drying time depends on the surface area and moisture content of the hydrogel-like crosslinked body, and the type of dryer, and is selected so as to achieve the desired moisture content. Incidentally, since it is difficult to reduce the moisture content of a water absorbent resin to zero, when a small amount of water (for example, 0.3 to 15% by weight, further 0.5 to 10% by weight) is contained in the water absorbent resin and it can be handled as a powder, the water absorbent resin containing this small amount of water is also referred to as a water absorbent resin in this specification. In the water absorbent resin of the present embodiment, the content of the crosslinked polyaspartic acid composition of the present embodiment is preferably 50% by mass to 100% by mass, more preferably 70% by mass to 100% by mass, and further preferably 90% by mass to 100% by mass. The water absorbent resin of the present embodiment may be the crosslinked polyaspartic acid composition of the present embodiment. (Water-absorbing resin particles)
[0057] The water-absorbent resin particles according to one embodiment of the present invention (the present embodiment) are made of the water-absorbent resin according to the present embodiment.
[0058] The shape of the water-absorbent resin particles of this embodiment may be substantially spherical, crushed, granular, etc. The size (average particle size) of the water-absorbent resin particles of this embodiment is preferably 1 to 5000 μm, more preferably 10 to 1000 μm, and further preferably 100 to 800 μm. The particle size distribution of the water-absorbent resin particles may be adjusted by performing an operation such as particle size adjustment using classification with a sieve.
[0059] The water-absorbent resin particles of the present embodiment can be crosslinked (surface crosslinked) on the surface of the crosslinked hydrogel using a crosslinking agent. By carrying out surface crosslinking, the water absorption properties of the water-absorbent resin particles can be easily controlled. The surface crosslinking is preferably carried out at a timing when the crosslinked hydrogel has a specific water content.
[0060] Examples of the crosslinking agent (surface crosslinking agent) for performing surface crosslinking include the crosslinking agent used in producing the crosslinked polyaspartic acid composition of the present embodiment. Other compounds having two or more reactive functional groups can also be mentioned. The crosslinking agent may be used alone or in combination of two or more kinds.
[0061] After the surface cross-linking, water or the water-containing solvent can be distilled off by a known method to obtain cross-linked particles which are a dry product having a cross-linked surface.
[0062] The water-absorbent resin particles of the present embodiment may be composed of only the crosslinked particles, but may further contain various additional components selected from, for example, a gel stabilizer, a metal chelating agent, and a flowability improver (lubricant). The additional components may be disposed inside the crosslinked particles, on the surface of the crosslinked particles, or both. As the additional component, a flowability improver (lubricant) is preferred, and among them, inorganic particles are more preferred. Examples of inorganic particles include silica particles such as amorphous silica, talc, and mica.
[0063] The water-absorbent resin particles may contain a plurality of inorganic particles arranged on the surface of the crosslinked particle. For example, the inorganic particles can be arranged on the surface of the crosslinked particle by mixing the crosslinked particle with the inorganic particles. The inorganic particles may be silica particles such as amorphous silica. When the water-absorbent resin particles contain inorganic particles arranged on the surface of the crosslinked particle, the ratio of the inorganic particles to the mass of the crosslinked particle may be 0.2 mass% or more, 0.5 mass% or more, 1.0 mass% or more, or 1.5 mass% or more, and may be 5.0 mass% or less, or 3.5 mass% or less. When the amount of the inorganic particles added is within the above-mentioned range, the water-absorbent resin particles having suitable water absorption properties are easily obtained. (Absorbent)
[0064] The absorbent body according to one embodiment of the present invention (the present embodiment) has water-absorbent resin particles and a fiber layer containing fibrous material. The absorbent body is, for example, a mixture containing water-absorbent resin particles and fibrous material. The absorbent body may have a configuration in which water-absorbent resin particles and fibrous material are uniformly mixed, a configuration in which water-absorbent resin particles are sandwiched between fibrous material formed in a sheet or layer, or other configurations.
[0065] The mass ratio of the water-absorbent resin particles in the absorbent body of the present embodiment may be 2 to 100 mass %, 10 to 90 mass %, or 10 to 80 mass % based on the total mass of the water-absorbent resin particles and fibrous materials.
[0066] The shape of the absorbent body of the present embodiment is not particularly limited, and may be, for example, a sheet, a tube, a film, or a fiber. The thickness of the absorbent body (for example, the thickness of a sheet-shaped absorbent body) may be, for example, 0.1 to 50 mm, or 0.3 to 30 mm.
[0067] The absorbent body of the present embodiment uses the water-absorbing resin particles of the present embodiment. The absorbent body of the present embodiment may use other known water-absorbing resin particles in addition to the water-absorbing resin particles of the present embodiment. It is preferable that the absorbent body of the present embodiment contains only the water-absorbing resin particles of the present embodiment as the water-absorbing resin particles.
[0068] The content of the water-absorbent resin particles in the absorbent body of the present embodiment is set to 50 to 2000 g per square meter of the absorbent body (i.e., 50 to 2000 g / m) from the viewpoint of more easily obtaining sufficient liquid absorption performance when the absorbent body is used in an absorbent article described later. 2 ), and more preferably 100 to 1000 g / m 2 In order to ensure that the absorbent article exhibits sufficient liquid absorption performance and, in particular, to suppress liquid leakage, the content of the water-absorbent resin particles is 50 g / m 2 From the viewpoints of suppressing the occurrence of the gel blocking phenomenon, exhibiting the liquid diffusion performance as an absorbent article, and further improving the liquid permeation speed, the content of the water-absorbent resin particles is preferably 2000 g / m or more. 2 It is preferable that: [Fibrous material]
[0069] The fibrous material is not particularly limited, but may be finely ground wood pulp, cotton, cotton linters, rayon, cotton, wool, acetate, vinylon, cellulosic fibers such as cellulose acetate, synthetic fibers such as polyamide, polyester, polyolefin, or mixtures of these fibers. The fibrous material may be used alone or in combination of two or more. Hydrophilic fibers may be used as the fibrous material.
[0070] The content of the fibrous material is set to 50 to 800 g per square meter of the absorbent body (i.e., 50 to 800 g / m2) from the viewpoint of obtaining sufficient liquid absorption performance even when the absorbent body is used in an absorbent article described later. 2 ), and more preferably 100 to 600 g / m 2 , and more preferably 150 to 500 g / m 2 In order to ensure that the absorbent article exhibits sufficient liquid absorption performance, in particular by suppressing the occurrence of the gel blocking phenomenon and enhancing the liquid diffusion performance, and further by enhancing the strength of the absorbent body after absorbing liquid, the content of the fibrous material is set to 50 g or more per square meter of the absorbent body (i.e., 50 g / m 2In particular, from the viewpoint of suppressing return of the absorbent after absorbing liquid, the content of the fibrous material is preferably 800 g or less per square meter of the absorbent body (i.e., 800 g / m 2 It is preferable that
[0071] In order to improve the shape retention of the absorbent before and during use, an adhesive binder may be added to the fibrous material to bond the fibers together. Examples of the adhesive binder include heat-fusible synthetic fibers, hot melt adhesives, adhesive emulsions, etc. The adhesive binder may be used alone or in combination of two or more kinds.
[0072] Examples of heat-fusible synthetic fibers include fully melted binders such as polyethylene, polypropylene, and ethylene-propylene copolymers; non-fully melted binders having a side-by-side or core-sheath structure of polypropylene and polyethylene, etc. In the above-mentioned non-fully melted binders, only the polyethylene portion can be heat-fusible.
[0073] Examples of hot melt adhesives include mixtures of base polymers such as ethylene-vinyl acetate copolymers, styrene-isoprene-styrene block copolymers, styrene-butadiene-styrene block copolymers, styrene-ethylene-butylene-styrene block copolymers, styrene-ethylene-propylene-styrene block copolymers, and amorphous polypropylene with tackifiers, plasticizers, antioxidants, and the like.
[0074] The adhesive emulsion may be, for example, a polymer of at least one monomer selected from the group consisting of methyl methacrylate, styrene, acrylonitrile, 2-ethylhexyl acrylate, butyl acrylate, butadiene, ethylene, and vinyl acetate. [Additives]
[0075] The absorbent of the present embodiment may further contain various additives, such as inorganic powders, deodorants, pigments, dyes, fragrances, antibacterial agents, and adhesives, which are commonly used in the technical field. These additives can impart various functions to the absorbent. Examples of the inorganic powders include silicon dioxide, zeolite, mica, kaolin, and clay. When the water-absorbent resin particles contain inorganic particles, the absorbent may contain inorganic powders in addition to the inorganic particles in the water-absorbent resin particles. (Absorbent articles)
[0076] An absorbent article according to one embodiment of the present invention (the present embodiment) includes an absorbent body, a liquid-permeable sheet arranged on the outermost side on the side into which the liquid to be absorbed will penetrate, and a liquid-impermeable sheet arranged on the outermost side on the side opposite to the side into which the liquid to be absorbed will penetrate. Examples of absorbent articles include diapers (e.g., paper diapers), toilet training pants, incontinence pads, urine absorption sheets, urine absorption liners, sanitary materials (sanitary napkins, tampons, etc.), sweat pads, pet sheets, parts for simple toilets, and animal waste treatment materials.
[0077] In the absorbent article, a liquid impermeable sheet, an absorbent body, and a liquid permeable sheet are layered in this order.
[0078] The absorbent article of the present embodiment uses the absorbent body of the present embodiment. The absorbent article of the present embodiment may use other known absorbents in addition to the absorbent body of the present embodiment. It is preferable that the absorbent article of the present embodiment uses only the absorbent body of the present embodiment as the absorbent body. [Liquid-permeable sheet]
[0079] The liquid-permeable sheet is disposed on the outermost side on the side into which the liquid to be absorbed penetrates. The liquid-permeable sheet has, for example, a main surface that is larger than the main surface of the absorbent body, and the outer edge of the liquid-permeable sheet extends around the periphery of the absorbent body.
[0080] The liquid-permeable sheet may be a sheet formed from a resin or fiber commonly used in the art. From the viewpoint of liquid permeability, flexibility and strength when used in an absorbent article, the liquid-permeable sheet may contain, for example, polyolefins such as polyethylene (PE) and polypropylene (PP), polyethylene terephthalate (PET), polytrimethylene terephthalate (PTT), polyethylene naphthalate (PEN), polybutylene adipate terephthalate (PBAT), polybutylene succinate (PBS), polybutylene succinate adipate (PBSA), polylactic acid, polyester such as polyhydroxyalkanoate, polyamide such as nylon, and synthetic resins such as rayon, or synthetic fibers containing these synthetic resins, or natural fibers including cotton, silk, hemp, or pulp (cellulose). From the viewpoint of increasing the strength of the liquid-permeable sheet, the liquid-permeable sheet may contain synthetic fibers. The synthetic fibers may be polyolefin fibers, polyester fibers, or a combination thereof. These materials may be used alone or in combination of two or more materials.
[0081] The liquid-permeable sheet may be a nonwoven fabric, a porous sheet, or a combination thereof. A nonwoven fabric is a sheet in which fibers are intertwined without being woven. The nonwoven fabric may be a nonwoven fabric made of short fibers (i.e., staples) (short fiber nonwoven fabric) or a nonwoven fabric made of long fibers (i.e., filaments) (long fiber nonwoven fabric). The staples may have a fiber length of, but is not limited to, typically several hundred mm or less.
[0082] The liquid permeable sheet may be at least one type of nonwoven fabric selected from the group consisting of thermal-bonded nonwoven fabric, air-through nonwoven fabric, resin-bonded nonwoven fabric, spunbonded nonwoven fabric, melt-blown nonwoven fabric, spunbonded / melt-blown / spunbonded nonwoven fabric, air-laid nonwoven fabric, spunlace nonwoven fabric, and point-bonded nonwoven fabric, and is preferably at least one type of nonwoven fabric selected from the group consisting of thermal-bonded nonwoven fabric, air-through nonwoven fabric, spunbonded nonwoven fabric, and spunbonded / melt-blown / spunbonded nonwoven fabric.
[0083] The liquid-permeable sheet may be a thermal bonded nonwoven fabric, an air-through nonwoven fabric, a resin bonded nonwoven fabric, a spunbonded nonwoven fabric, a melt-blown nonwoven fabric, an air-laid nonwoven fabric, a spunlace nonwoven fabric, a point-bonded nonwoven fabric, or a laminate of two or more nonwoven fabrics selected from these. These nonwoven fabrics may be, for example, those formed from the above-mentioned synthetic fibers or natural fibers. The laminate of two or more nonwoven fabrics may be, for example, a spunbonded nonwoven fabric, a melt-blown nonwoven fabric, and a spunbonded nonwoven fabric, which are composite nonwoven fabrics laminated in this order, such as a spunbonded / melt-blown / spunbonded nonwoven fabric. Among these, from the viewpoint of suppressing liquid leakage, a thermal bonded nonwoven fabric, an air-through nonwoven fabric, a spunbonded nonwoven fabric, or a spunbonded / melt-blown / spunbonded nonwoven fabric is preferably used.
[0084] It is desirable for the nonwoven fabric used as the liquid permeable sheet to have an appropriate hydrophilicity from the viewpoint of the liquid absorbing performance of the absorbent article.
[0085] The hydrophilic nonwoven fabric described above may be formed of fibers exhibiting a moderate degree of hydrophilicity, such as rayon fibers, or may be formed of fibers obtained by hydrophilizing hydrophobic chemical fibers, such as polyolefin fibers and polyester fibers. Methods for obtaining a nonwoven fabric containing hydrophobic chemical fibers that have been hydrophilized include, for example, a method of obtaining a nonwoven fabric by a spunbonding method using a mixture of hydrophobic chemical fibers and a hydrophilizing agent, a method of accompanying a hydrophilizing agent when preparing a spunbonded nonwoven fabric from hydrophobic chemical fibers, and a method of impregnating a spunbonded nonwoven fabric obtained by using hydrophobic chemical fibers with a hydrophilizing agent. Examples of hydrophilizing agents include anionic surfactants such as aliphatic sulfonates and higher alcohol sulfate salts, cationic surfactants such as quaternary ammonium salts, nonionic surfactants such as polyethylene glycol fatty acid esters, polyglycerin fatty acid esters, and sorbitan fatty acid esters, silicone surfactants such as polyoxyalkylene-modified silicones, and stain release agents made of polyester, polyamide, acrylic, and urethane resins.
[0086] The liquid-permeable sheet is preferably a nonwoven fabric that is appropriately bulky and has a large basis weight, from the viewpoint of imparting good liquid permeability, flexibility, strength and cushioning to the absorbent article, and from the viewpoint of increasing the liquid permeation rate of the absorbent article. [Liquid-impermeable sheet]
[0087] The liquid-impermeable sheet is disposed on the outermost side of the absorbent article opposite the liquid-permeable sheet. The liquid-impermeable sheet has, for example, a main surface wider than the main surface of the absorbent body, and the outer edge of the liquid-impermeable sheet extends around the periphery of the absorbent body. The liquid-impermeable sheet prevents liquid absorbed in the absorbent body from leaking out from the liquid-impermeable sheet side to the outside.
[0088] Examples of the liquid-impermeable sheet include sheets made of resins such as polyethylene, polypropylene, polyvinyl chloride, polylactic acid, and polyhydroxyalkanoate, sheets made of nonwoven fabrics such as spunbond / meltblown / spunbond (SMS) nonwoven fabrics in which a water-resistant meltblown nonwoven fabric is sandwiched between high-strength spunbond nonwoven fabrics, and sheets made of composite materials of these resins and nonwoven fabrics (e.g., spunbond nonwoven fabrics and spunlace nonwoven fabrics). The liquid-impermeable sheet is preferably breathable from the viewpoint of reducing stuffiness when worn and reducing discomfort to the wearer. As the liquid-impermeable sheet, a sheet made of a synthetic resin mainly composed of low-density polyethylene (LDPE) resin can be used.
[0089] The size relationship between the absorbent body, the liquid permeable sheet, and the liquid impermeable sheet is not particularly limited, and may be appropriately adjusted depending on the application of the absorbent article, etc. EXAMPLES
[0090] The present invention will be described in detail below with reference to examples, but the present invention is not limited thereto.
[0091] (Reaction Apparatus) Continuous kneader: "KRC kneader" manufactured by Kurimoto Iron Works Ltd. Vacuum dryer: AS ONE Corporation Cone type dryer: Ribocone, manufactured by Okawara Manufacturing Co., Ltd. Vibratory dryer: manufactured by Chuo Kakoki Fluidized bed dryer: Manufactured by Kurimoto Iron Works Ltd.
[0092] (Measurement method) [Method for measuring weight average molecular weight] The weight-average molecular weight (Mw) of polysuccinimide was measured by gel permeation chromatography (GPC) using polysaccharide polymer (pullulan) as the standard after dissolving the polysuccinimide in 15% aqueous sodium hydroxide solution. Equipment: HLC-8420GPC (Tosoh Corporation) Detector: Differential refractometer Column: Shodex Asahipak Guard column GF-1G 7B, GF-7MHQ x 3, Reference column: SB-800HQ x 3 Solvent: 0.1M saline Concentration: 0.2 to 1.0 wt% Injection volume: 10μL Flow rate: 1.0ml / min
[0093] [Method for measuring dicarboxylic acid content] Manufactured by JEOL Ltd. 1 The amount of dicarboxylic acid was measured using HNMR. 0.1 g of polysuccinimide sample was dissolved in 0.6 mL of deuterated dimethyl sulfoxide to prepare a measurement sample, which was then measured at 60°C. 1 From the HNMR spectrum results, the amounts of the main chain peak, the terminal group peak such as a dicarboxyl group, the maleimide terminal group peak, and the peaks due to side reactions such as the succinimide terminal group peak were identified, and the amount of dicarboxyl groups was calculated from the proportion of the total.
[0094] Example 1 "1st process" A mixture of 1 mol of L-aspartic acid and 60 mol % of 85% phosphoric acid was mixed using a continuous kneader "KRC kneader" manufactured by Kurimoto Iron Works Co., Ltd., as follows. The heat medium was set to 195°C, the screw speed was set to 30 rpm, nitrogen was fed at 10 L / min, and the mixture of aspartic acid and phosphoric acid obtained above was fed so that the discharge rate was 1 kg / h to perform polycondensation, and a solid polymer (polysuccinimide composition containing first polysuccinimide) with a slight brownish color was obtained. The time from feeding the raw materials to the first discharge from the outlet was about 10 minutes. After pulverizing the solid polymer with an electric grinder, the powder was washed three times with ion-exchanged water in an amount three times its weight to remove phosphoric acid, and the molecular weight was measured by GPC, and the weight average molecular weight of this first polysuccinimide was 26,400. The solid polymer (polysuccinimide composition containing the first polysuccinimide) thus obtained is subjected to the following steps: 1The amount of dicarboxylic acid measured by H-NMR was 3.7 mol %. The results are shown in Table 1.
[0095] "Second process" The polymer obtained in the first step (polysuccinimide composition containing the first polysuccinimide) was pulverized with an electric pulverizer, and then subjected to dehydration condensation in a vacuum dryer to elongate the molecular weight. Polymerization was performed for 6 hours at a set temperature of 190°C and a vacuum degree of 1333 Pa to obtain an unbranched polysuccinimide having a molecular weight of 127,300. The presence or absence of branching can be determined, for example, by using a known method (Non-Patent Document B): 1 This can be determined by measuring the amount of amide NH in H NMR. It was confirmed that the amount of NH was 0 based on the peak amount at 8.1-9.2 ppm, and it was determined that there was no branching.
[0096] [Non-patent document B] Macromolecules, Vol.30, No.8, 1997 pp2305-2312.
[0097] (Examples 2 to 6, Comparative Examples 1 to 2, 4 to 5) Polysuccinimides of Examples 2 to 6 and Comparative Examples 1 to 5 were obtained in the same manner as in Example 1, except for the reaction conditions in the first step and the reaction conditions in the second step shown in Table 1. The reaction conditions in the first step in Examples 2, 4, 5, and 6 were the same, but the physical properties of the obtained polysuccinimides differed due to changes in the screw configuration of the continuous kneader. The amount of dicarboxylic acid in the polysuccinimide composition obtained in the first step and the weight average molecular weight of the first polysuccinimide contained in the polysuccinimide composition were measured in the same manner as in Example 1. The weight average molecular weight of the second polysuccinimide obtained in the second step was also measured. The results are shown in Table 1. In Comparative Examples 4 and 5, the apparatus was stopped in the second step, and the step was stopped without flowing, so that a polysuccinimide composition containing the second polysuccinimide was not obtained.
[0098] Comparative Example 3 In the second step, the polymer obtained in the first step (polysuccinimide composition containing the first polysuccinimide) was reacted again in a continuous kneader under the reaction conditions shown in Table 1 to obtain the polysuccinimide shown in Comparative Example 3. The weight average molecular weight of the polysuccinimide obtained in the second step was measured. No significant increase in the weight average molecular weight was observed.
[0099] [Table 1] The meaning of symbols in Table 1 CK: Continuous kneader "KRC kneader" manufactured by Kurimoto Iron Works Ltd. VD: Vacuum dryer, manufactured by AS ONE Corporation CD: Cone-type dryer, manufactured by Okawara Manufacturing, Ribocone VrD: Vibratory dryer manufactured by Chuo Kakoki FD:Fluidized bed dryer
[0100] (Consideration) As seen from Table 1, in Examples 1 to 7, in the first step, a mixture of aspartic acid and phosphoric acid was polycondensed to obtain a polysuccinimide composition containing a first polysuccinimide having a weight average molecular weight of 25,000 to 50,000. Using this polysuccinimide composition as it is, in the second step, the molecular weight was increased to produce a polysuccinimide composition containing a second polysuccinimide having a weight average molecular weight of 100,000 to 150,000.
[0101] On the other hand, in Comparative Examples 1 and 2, the weight average molecular weight of the first polysuccinimide obtained in the first step exceeded 50,000. The polysuccinimide composition containing the second polysuccinimide produced using the polysuccinimide composition could not be made high molecular weight, and had a weight average molecular weight of 80,000 or less. This is presumed to be because the amount of dicarboxylic acid in the polysuccinimide containing the first polysuccinimide obtained in the first step was insufficient, so that the increase in molecular weight did not progress in the chain extension reaction in the second step. It is also found that a high molecular weight polymer cannot be obtained even if the reaction is carried out again in a continuous kneader in Comparative Example 3.
[0102] In Comparative Examples 4-5, the weight average molecular weight of the first polysuccinimide obtained in the first step was less than 25,000. The reaction in the second step was carried out using the polysuccinimide composition, but the apparatus stopped or the composition did not flow and stopped, and the final product was not obtained. The first polysuccinimide containing phosphoric acid and having a molecular weight of about 20,000 obtained in the first step became very viscous at a reaction temperature of 190°C, so that in addition to the aggregation of powders, adhesion to the stirring blades and reaction walls was very likely to occur, and the powder did not flow in a fluidized bed dryer, and the torque of the stirring blade rotation in a rotary dryer increased significantly, which was a factor in not being able to continue the reaction. On the other hand, in Examples 5 and 6, a mixture of aspartic acid and phosphoric acid was polycondensed in the first step to obtain polysuccinimide with a weight average molecular weight of 25,000 or more. Generally, the molecular weight of a polymer affects the Tg of the polymer, and the higher the molecular weight, the higher the Tg. The increase in Tg is very sensitive to the aggregation of powders and adhesion to the reactor. It is presumed that this difference led to the fact that the molecular weight could be extended using a drying device in Examples 5 and 6, but was stopped in Comparative Examples 4 and 5, and the final product could not be obtained.
Claims
1. A method for producing a polysuccinimide, comprising producing a second polysuccinimide from a polysuccinimide composition containing a first polysuccinimide, the method comprising the steps of: a chain extension step of carrying out a chain extension reaction of the first polysuccinimide to obtain the second polysuccinimide, The first polysuccinimide has a weight average molecular weight (Mw) in the range of 25,000 to 50,000, and the proportion of dicarboxylic acid in the polysuccinimide composition is 1.5 to 4 mol %.
2. The chain extension step is a second step, and before the chain extension step, as a first step, The method further includes a polycondensation step of performing a polycondensation reaction of aspartic acid to obtain a polysuccinimide composition containing the first polysuccinimide, 2. The method for producing polysuccinimide according to claim 1, wherein the first step and the second step are carried out in different apparatuses.
3. 3. The method for producing polysuccinimide according to claim 2, wherein the first step is terminated and the second step is started at a stage where the weight average molecular weight (Mw) of the first polysuccinimide in the first step is in the range of 25,000 to 50,000 and the ratio of dicarboxylic acid in the first polysuccinimide is in the range of 1.5 to 4 mol %.
4. 4. The method for producing polysuccinimide according to claim 2 or 3, wherein the first step is carried out using a continuous kneader.
5. 3. The method for producing polysuccinimide according to claim 1 or 2, wherein the chain extension step is carried out using at least one device selected from the group consisting of a hot air transport type dryer, a material agitation type dryer, a fluidized bed dryer, a material conveying and stationary type dryer, a cylindrical dryer, an infrared dryer, a microwave dryer, and a superheated steam dryer.
6. The polysuccinimide is obtained by the method for producing polysuccinimide according to claim 1 or 2, A polysuccinimide composition containing a second polysuccinimide having a weight average molecular weight in the range of 100,000 to 500,000.
7. A polyaspartic acid composition which is a hydrolyzate of the polysuccinimide composition according to claim 6.
8. A crosslinked polyaspartic acid composition which is a crosslinking reaction product of the polyaspartic acid composition according to claim 7.
9. A cosmetic thickener comprising the crosslinked polyaspartic acid composition according to claim 8.
10. A water-absorbing composition comprising the crosslinked polyaspartic acid composition according to claim 8.
Citation Information
Patent Citations
Production of amino acid polycondensate and biodegradable polypeptide hydrolyzate thereof,and use of those in cleaningcomposition
JP1996231710A
Production of polysuccinimide
JP1997302088A
Production method of polysuccinimide
JP2001335635A